MHDiff: Memory- and Hardware-Efficient Diffusion Acceleration via Focal Pixel Aware Quantization - Qi, Chunyu; Wang, Xuhang; Chen, Ruiyang; Yao, Yuanzheng; Jing, Naifeng; Zhang, Chen; Wang, Jun; Fu, Zhihui; Liang, Xiaoyao; Song, Zhuoran (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Diffusion models have demonstrated superior performance in image generation tasks, thus becoming the mainstream model for generative visual tasks. Diffusion models need to execute multiple timesteps sequentially, resulting in a dramatic increase in workload. Existing accelerators leverage the data similarity between adjacent timesteps and perform mixed-precision differential quantization to accelerate diffusion models. However, merging differential values with raw inputs in each layer of each timestep to ensure computational correctness requires significant memory access for loading raw inputs, which creates a heavy memory burden. Moreover, mixed-precision computations may lead to low hardware utilization if not well designed. Unlike these works, we propose MHDiff, a tailored framework that identifies the focal pixels at the first layer and finetunes them to fit all layers, then represents focal pixels with high-precision while using low-precision for others, thereby accelerating diffusion models while minimizing memory burden. To improve hardware utilization, MHDiff employs a packing module that merges low-precision values into high-precision values to create full high-precision matrices and designs a processing element (PE) array to efficiently process the packed matrices. Extensive experiment results demonstrate that MHDiff can achieve satisfactory performance with negligible quality loss.